Conceptual approaches to formation of the improved model for prophylaxis of school traumatism - Mikhalchuk, V. M.; Bondar, S. O. (Journal of Education, Health and Sport, 2018)
Conceptual approaches for the formation of schoolchildren’s safe behavior based on a personality-oriented principle with determination of readiness and ability to adhere to the culture of health are presented in this essay. The stages and their components of organizational measures for creating a favorable environment for this are proposed. There are substantiated six structural blocks (administrative, scientific regulation, conceptual, content, technological, diagnostic and productive), as for the improvement of the model of school traumatism.